Sistem Pelayanan Calon Pekerja Migran Indonesia (CPMI) di Dinas Koperasi dan Tenaga Kerja Kabupaten Boyolali - Novi Gita Rachmawati; Fahmi Ulin Ni’mah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to examine the service system for Indonesian Migrant Worker Candidates (CPMI) at the Office of Cooperatives and Manpower of Boyolali Regency, with particular emphasis on identity verification and placement agreement services. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The analysis focuses on service procedures, compliance with public service standards, and the obstacles encountered during the service process. The findings indicate that the service system has generally been implemented in accordance with public service standards as stipulated in Law Number 25 of 2009 on Public Services. Service procedures, requirements, service duration, and the attitudes of service officers have supported the overall effectiveness of the CPMI application process. Nevertheless, several administrative and technical challenges were identified, especially regarding incomplete documentation submitted by CPMI and limited understanding of how to independently operate the SIAPKerja digital system. These issues often lead to delays in service delivery and require additional assistance from service officers. Therefore, this study concludes that although the service system has functioned relatively effectively, further improvements are needed, particularly in strengthening digital outreach, enhancing user guidance, and providing more intensive assistance throughout the application process to achieve more optimal and inclusive service outcomes.